Moving in Circles along a Straight Path: The Elusiveness of Inclusive Education in Early Childhood Development in Uganda - Ejuu, Godfrey (Journal of Childhood & Developmental Disorders, 2016)
Children with disability have for long been treated with suspicion in many African communities. Some of them are usually treated either with reverence or contempt depending on the disability [1]. For example, children with albinism are revered because it is believed that their body parts have great magical powers, thus, concoctions made from albino body parts can make one rich [2]. Children with different forms of mental retardation are treated with contempt because it is believed that they are a curse to the family handed down by the gods for the family’s misdeeds [3]. To these people, such children must be mistreated or neglected because helping them will be interfering with justice that the gods have handed to such a family [1]. For fear of the justice from the gods, there are many reported cases where parents, especially men have abandoned their homes after fathering a child with disability [4]. Within the homes, these children suffer ridicule from family members; some are tortured or neglected by their parents or guardians resulting in malnutrition and death
Keywords: Elusiveness; Inclusive Education; Early Childhood Development